Formation of relations between the enterprise and consumers as the basis of the industrial enterprise development - Raiko, D. V.; Tseitlin, L. M. (Prague Institute for Qualification Enhancement, 2016)
Nowadays life makes the companies think about their existence: for whom and for what they work, from whom and from what depends their well-being and what it is necessary to do to become competitive and prof-itable. In order to prevent the destruction of the enterprise in certain periods it is necessary to know the typical problems and mistakes of organizations in this section of road. It is necessary to understand the nature of changes that occur in the enterprise and around it, to watch closely the factors that ensure the success of the organization, and do not miss the moment of introduction of changes.
Формування взаємовідносин між підприємством та споживачами як основа розвитку промислового підприємства
Keywords: relationship; enterprise; consumers